Corn Yield and Soil Fertility with Combined Use of Raw or Composted Beef Manure and Inorganic Fertilizers on the Texas Northern High Plains. Issue 2 (3rd April 2018) - Parker, David; Venhaus, Dave; Robinson, Clay; Marek, Thomas; Sweeten, John
ABSTRACT: About 7 million beef cattle are raised annually in the Texas High Plains, producing 16 million Mg of manure, which is land-applied as raw manure (RM) to crops. An interest in aerobic composting prompted a 2-year field study with the primary objective of evaluating corn ( Zea mays L.) yield and soil fertility for RM as compared to composted manure (CM). The four treatments (TRT) consisted of low-rate composted manure (CM-L), high-rate composted manure (CM-H), RM, and inorganic fertilizer (IN). All four TRT received equal plant—available N by supplementing the RM and CM with IN. Yield was measured by both machine-harvesting and hand-harvesting methods. Machine-harvested yield was similar among TRT for both years. Hand-harvested yield was lower for IN than RM in the first year, with similar yields among TRT in the second year. Due to drought, yields were considerably lower in the second year for all TRT. After 2 years, CM-H had higher soil P, K, Zn, and organic carbon concentrations than IN, with no differences among TRT for soil NO3 -N, pH, or electrical conductivity. Both CM and RM provided beneficial nutrients for corn production and improving soil fertility. Land application of CM and RM provides long-term benefits to soil health and sustainability in the Texas High Plains region.